The nexus between job satisfactions and human resource management (HRM) practices: a perceptual analysis of commercial banks in Bangladesh - Abdul, Mohani; Rahman, Mohammad Mizanur; Ali, Noor Azman; Mansor, Zuraina; Uddin, Mohammad Jamal; Rahaman, Md. Saidur (Faculty of Economics and Management, Universiti Putra Malaysia, 2018)
Employee motivation and continual productivity largely come from employee job satisfaction. The concept of job satisfaction in the workplace is still a burning and researching issue in the field of Human Resource Management (HRM) and Organizational Behavior. This research aims at describing employee perceived experience on HRM practices of three sectors within commercial banks in Bangladesh and their linkage with employee job satisfaction. A cross-sectional survey has been conducted on 150 employees at 30 bank branches by a structured self-administered questionnaire. Independent and dependent variables were measured by the Five-Point Likert-Type scale. Various statistical measures and tests like descriptive statistics, Duncan’s Multiple Range Mean test, correlation and multiple regression analysis were conducted too for the expected findings. Results proved that seven HRM practices out of nineteen e.g., training and development, creativity and innovation, benefits and services, manpower planning, promotional opportunity, the attitude of management, and work environment were found to be significant as predictors to banks’ employee job satisfaction and no distinct HRM practice was found as a significant predictor of job satisfaction for all three categories of the bank. So, the policymakers of commercial banks should consider these HRM policies and practices for employee better job satisfaction.